(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Cardiovascular disease constitute a major cause of death worldwide .inflamatory and anti inflamatory cytokines plays an important role in atherosclerosis formation and function of endothelial cells ; one the presentation of athrosclerosis and endothelial dysfunction is Slow coronary flow(SCF) syndrome and treatment of SCF patients has always been challenging , erythropoietin as a cytoprotective cytokine and also thorombotic factor can play a role in the prevention or progression of coronary events by effect on endothelial cells, due to dual physiological function of this hormone ,we will compare the blood level of erythropoietin in three different groups of patients who underwent angiography to find out its effect. Materials and methods: This cross-sectional study was performed on 173 candidats patients for angiography at Shafa Hospital in Kerman. the patient's serum erythropoietin measured by SANDWICH method and STATFOX ELISA device. Coronary angiography of patients was performed by Seldinger technique ,patients were classified into three groups: normal coronary artery (n = 50), SCF patients (n = 55) and coronary artery obstructive patients (n = 68). Data were analyzed using SPSS / 18 software. Results: In the SCF group, 50.9% (n=28) were female, in the coronary artery occlusion group, 63.2% (n=43) were male and , and in the normal group, 62% (n=31) were female (P = 0.024). The coronary artery occlusion and SCF patients show higher history of diabetes than normal coronary artery subjects (P = 0.027). Mean and standard deviation of erythropoietin were 53.3 ± 61.6 pg / ml, 72.8 ±134.4 pg / ml and 61.6 ± 109.5 pg / ml (P = 0.646) in normal coronary arteries, SCF patients and coronary artery disease patients, respectively. The coefficient of determination of erythropoietin in the regression model was 34.5%.